2019
DOI: 10.1177/1938640019863277
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal Tunnel Syndrome Secondary to Accessory Musculature: A Case Report

Abstract: Tarsal tunnel syndrome (TTS) is a relatively uncommon compression neuropathy caused by impingement of the tibial nerve or one of the terminal branches. The presence of accessory musculature at the posteromedial aspect of the ankle has been identified as a rare cause of this condition. Despite the rarity of this condition, it must be considered in patients with refractory symptoms consistent with tibial nerve dysfunction. The accurate diagnosis of this condition relies heavily on a detailed history and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Prolonged distal motor and sensory latency findings occur for tibial trap neuropathy at the tarsal level (28,29). In our data, it was found that there was a difference in the tibial nerve compared to the control group, although it was within normal limits.…”
Section: Discussionmentioning
confidence: 38%
“…Prolonged distal motor and sensory latency findings occur for tibial trap neuropathy at the tarsal level (28,29). In our data, it was found that there was a difference in the tibial nerve compared to the control group, although it was within normal limits.…”
Section: Discussionmentioning
confidence: 38%
“…However, a growing number of recent case reports implicating accessory anatomy as the etiology for compression at the tarsal tunnel suggest this may not be as rare as it was thought. Neary et al [ 13 ] consider this is due to increased implementation of an ankle MRI in routine diagnosis and increased surveillance for accessory muscles in that region. Doda et al [ 7 ] state that the key to diagnosing ASM is registering an MRI signal that is typical for a well-encapsulated skeletal muscle situated in an atypical anatomic location.…”
Section: Discussionmentioning
confidence: 99%
“…Kinoshita et al [ 12 ] reported on a case with TTS caused by ASM, in which they did a complete decompression of the tibial nerve combined with resection of ASM. Neary et al [ 13 ] presented a case in which the patient had refractory symptoms caused by tibial nerve compression. In that patient, both flexor digitorum accessories longus and ASM were identified and completely resected, followed by a tibial nerve decompression [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarsal tunnel syndrome is a painful foot condition caused by compression of the tibial nerve within the tarsal tunnel (43,44). This syndrome is more prevalent in women than in men and is induced by various factors, such as poorly fitting shoes, trauma, tarsal coalition, anatomic-biomechanical abnormalities such as rearfoot valgus or varus, postoperative scarring, lower extremity edema, systemic inflammatory arthropathies, diabetes, tenosynovitis, perineural fibrosis, osteophytes, hypertrophic retinaculum, and neuroma (45).…”
Section: Tarsal Tunnel Syndromementioning
confidence: 99%